Revitalizing Character Education Curricula in The Digital Era: A Literature Review at The Junior High School Level - Pramesti, Azzahra Maya; Nurhidayah, Rika; Firdaus, Miftahul; Khuriyah (Sunan Kalijaga International Journal on Islamic Educational Research, 2025)
This article examines the urgency of revitalizing character education curricula at the junior high school (SMP) level in response to profound transformations driven by digital culture. The study aims to analyze existing models of character education implementation, identify the impacts of the digital era on students’ character formation, explore emerging challenges, and propose strategic directions for curriculum revitalization. Employing a qualitative descriptive literature review design, this study systematically analyzed peer-reviewed articles, academic books, and policy documents published over the last decade, sourced from reputable digital databases. The findings indicate that character education in Indonesian SMPs has been institutionally implemented through integrated intrakurikular, kokurikular particularly the Projek Penguatan Profil Pelajar Pancasila (P5) and ekstrakurikular pathways grounded in Pancasila values and national education policy. While digital culture offers opportunities to enhance creativity, collaboration, and digital literacy, it simultaneously poses risks to students’ discipline, self-control, empathy, and integrity when not accompanied by adequate guidance. The study further identifies persistent challenges related to teacher preparedness, digital safety, cyberbullying, plagiarism, and assessment systems that remain predominantly oriented toward offline behavior. The implications of this study highlight the need to reconceptualize character education as a holistic integration of moral values, digital ethics, and civic responsibility, and to explicitly embed these dimensions within curriculum standards and assessment frameworks. As a limitation, this study relies on secondary data and does not capture direct empirical evidence from school practices. Future research is recommended to conduct empirical investigations that assess the effectiveness of digitally integrated character education models and explore the lived experiences of teachers and students in digital learning environments.